Targeting the Real Exchange Rate : Theory and Evidence - Vegh Gramont, Carlos; Calvo, Guillermo; Reinhart, Carmen (Washington, D.C. : International Monetary Fund, 1994)
This paper presents a theoretical and empirical analysis of policies aimed at setting a more depreciated level of the real exchange rate. An intertemporal optimizing model suggests that, in the absence of changes in fiscal policy, a more depreciated level of the real exchange can only be attained temporarily. This can be achieved by means of higher inflation and/or higher real interest rates, depending on the degree of capital mobility. Evidence for Brazil, Chile, and Colombia supports the model's prediction that undervalued real exchange rates are associated with higher inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet